2022
DOI: 10.2147/ndt.s383093
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Cognitive Impairment: Current Understanding of Its Neurobiology and Diagnosis

Abstract: Background Eye movement is critical for obtaining precise visual information and providing sensorimotor processes and advanced cognitive functions to the brain behavioral indicator. Methods In this article, we present a narrative review of the eye-movement paradigms (such as fixation, smooth pursuit eye movements, and memory-guided saccade tasks) in major depression. Results Characteristics of eye movement are considered to reflect several as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 122 publications
0
3
0
Order By: Relevance
“…Numerous studies have reported cognitive impairment in patients with MDD, including deficits in executive function, processing speed, memory, and attention (reviewed by [ 49 , 50 , 51 , 52 ]). A global assessment of cognitive abilities using the MoCA test also shows impairment in MDD patients [ 53 , 54 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have reported cognitive impairment in patients with MDD, including deficits in executive function, processing speed, memory, and attention (reviewed by [ 49 , 50 , 51 , 52 ]). A global assessment of cognitive abilities using the MoCA test also shows impairment in MDD patients [ 53 , 54 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another distinctive feature of cognitive impairment in MDD is impairments in executive function and processing speed detected by the TMT and Stroop task [ 49 , 50 , 51 , 52 , 65 ]. We also found a significant increase in processing speed with a higher accuracy in the TMT in the PCD patients compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…Neurocognitive impairment is present in 85-94% of cases during an MDE and 39-44% of cases during remissions. It mainly involves attention, short-term memory, and executive function and accounts for a disproportionately high percentage of patients who have not completely reached the psychosocial functioning they used to have before the onset of the MDE (22)(23)(24). A better identification and characterization of patients with MDD with neurocognitive dysfunction might promote the development of new and personalized treatments (25).…”
Section: Major Depressive Disordermentioning
confidence: 99%
“…MDD is characterized by a depressive mood bending lasting longer than 2 weeks. It describes a dramatic scenario in which emotional compunction meets social dysfunction, health issues and suicidal ideation [1]. It can be associated also with psychosis [2], representing, this latter, the delusional-hallucinatory hypostasis of the emotional atmosphere.…”
Section: Introductionmentioning
confidence: 99%